King Arthur and the Round Table - Talbott, Hudson (New York : Morrow Junior Books, 1995)
Retells the story of how the young Arthur became High King of all Britain and assembled his Knights of the Round Table.
"Books of wonder."
edited hb 2015-06-16
Keywords: Arthur, -- King -- Legends; Arthurian romances -- Adaptations; Folklore -- England; Knights and knighthood -- Folklore